Double primary malignant tumor in a centenarian female: Case report and review of literature - Shrivastava, Ankur K; Nanda, Siddhartha (Nepalese Journal of Ophthalmology, 2019)
A hundred and three year old female patient was evaluated for ulcer over the nasion area and a mass arising from the right upper eyelid, appearing two months apart. Histopathology revealed nasion ulcer as basal cell carcinoma while right eyelid mass was diagnosed as poorly differentiated squamous cell carcinoma. Based on these findings and the time gap between two lesions a diagnosis of synchronous double primary malignant tumor was made. Although the prevalence of multiple primary malignant tumor is highest in breast, colo-rectum and prostate cancer we report a rare case of double primary malignant tumor of the eyelid and nasion in a centenarian female.